Reassessment of the upper Maastrichtian material from Chile referred to Mauisaurus Hector, 1874 (Plesiosauroidea: Elasmosauridae) and the taxonomical value of the hemispherical propodial head among austral elasmosaurids - Otero, R. A.; O'gorman, Jose Patricio; Hiller, N. (New Zealand Journal of Geology and Geophysics)
The femoral hemispherical articular head was regarded as autapomorphic of Mauisaurus haasti Hector, 1874 from the upper Campanian of New Zealand. Review of three Maastrichtian taxa, Aristonectes quiriquinensis from Chile, Aristonectes sp. from Antarctica and Kaiwhekea katiki from New Zealand, reveals that the femoral hemispherical head is a common character among aristonectines. This feature can therefore be discarded as an autapomorphy of Mauisaurus haasti. Propodials of A. quiriquinensis are shown to be the same as those in two coeval Chilean specimens previously referred to Mauisaurus sp.; in consequence, these are now referred to A. quiriquinensis. Additionally, specimens referred to A. quiriquinensis allow confirmation that during ontogeny the humerus and the femur change from a flat capitulum in juveniles to hemispherical heads of both the humeri and femora in the adult stage. The evidence shows that the presence of Mauisaurus along the southeastern Pacific margin cannot be verified to date. Fil: Otero, R. A. Museo Nacional de Historia Natural de Santiago; Chile Fil: O'gorman, Jose Patricio. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Hiller, N. University Of Canterbury; Nueva Zelanda